2021
DOI: 10.1007/s10654-021-00747-3
|View full text |Cite
|
Sign up to set email alerts
|

Vegetable nitrate intake, blood pressure and incident cardiovascular disease: Danish Diet, Cancer, and Health Study

Abstract: Whether the vascular effects of inorganic nitrate, observed in clinical trials, translate to a reduction in cardiovascular disease (CVD) with habitual dietary nitrate intake in prospective studies warrants investigation. We aimed to determine if vegetable nitrate, the major dietary nitrate source, is associated with lower blood pressure (BP) and lower risk of incident CVD. Among 53,150 participants of the Danish Diet, Cancer, and Health Study, without CVD at baseline, vegetable nitrate intake was assessed usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 44 publications
1
37
2
Order By: Relevance
“…Now it is believed that nitrate may also have a positive effect. Bondonno et al [19] conducted clinical trials and found that a moderate vegetable nitrate intake was associated with 12-26% lower risk of hospitalisations due to ischaemic heart disease, heart failure, ischaemic stroke and peripheral artery disease. According to these authors, the daily consumption of at least 60 mg of vegetable nitrate may mitigate the risk of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Now it is believed that nitrate may also have a positive effect. Bondonno et al [19] conducted clinical trials and found that a moderate vegetable nitrate intake was associated with 12-26% lower risk of hospitalisations due to ischaemic heart disease, heart failure, ischaemic stroke and peripheral artery disease. According to these authors, the daily consumption of at least 60 mg of vegetable nitrate may mitigate the risk of cardiovascular disease.…”
Section: Introductionmentioning
confidence: 99%
“…Despite known beneficial associations of cardiovascular health with long-term intake of leafy vegetables (the primary contributor to dietary NO 3 − intake, although confounded with intake of phenolic compounds) [ 8 ], experimental studies of this relationship have tended to be short-term, less than 70 days [ 1 ]. However, whilst useful for elucidation and/or confirmation of mechanisms, short-term studies cannot predict long-term effects, and studies using enriched supplements cannot predict effects of actual foods [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The scarcity of data comparing physiologically relevant intakes of phenolics with NO 3 − , may reflect the practical difficulties of this research. Intakes of NO 3 − and phenolics are difficult to distinguish in observational studies, because vegetables are major sources of both these compound types [ 8 ]; and in contrast to NO 3 − , many phenolic compounds are costly to isolate and difficult to study as pure compounds without substantially changing their bioavailability and probably other properties [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…128 Most recently, the Danish Diet, Cancer and Health (DDCH) study with 23 years of follow-up reported that moderate vegetable nitrate intake (∼60 mg day −1 = 1 cup of green leafy vegetables) was linked with 12%, 15%, 17% and 26% lower risk of ischemic heart disease, heart failure, ischemic stroke, and peripheral artery disease hospitalizations, respectively. 129 The disparate results of the American Nurses’ Health cohort study compared to the other three Australian cohort studies and the Danish cohort study could potentially be explained by the nitrate databases used to quantify intakes. Specifically, the nitrate database used by the American Nurses’ Health cohort study was less comprehensive 128 than the newer version utilised by the other four studies.…”
Section: Nitrate and Cardiovascular Diseasementioning
confidence: 99%